Fluoroscopy Guided Percutaneous Transpedicular Biopsy for Thoracic and Lumbar Vertebral Body Lesion: Technique and Safety in 23 Consecutive Cases - Shrestha, D.; Shrestha, R.; Dhoju, D (Kathmandu University Medical Journal, 2017)
Background Though some vertebral lesions have typical imaging findings, histological/ microbiological evidence are required for definitive diagnosis and management, specially for tumor and infective lesions so that wrong diagnosis and wrong treatment can be avoided. Conventionally, open biopsy methods are used. With availability of CT scan, MRI, percutaneous transpedicular vertebral biopsy has now become popular as a minimally invasive technique for biopsy of vertebral lesion.Objective To describes technique and to analyzes safety and feasibility of percutaneous transpedicular vertebral biopsy with fluoroscopy guidance for thoracic and lumbar vertebral body lesions.Method Twenty three patients who underwent percutaneous transpedicular vertebral biopsy under fluoroscopy guidance were retrospectively evaluated for demographic data, indication for biopsy, anatomical locations, histological/microbiological diagnosis, complications and final outcome of treatment. True positive, true negative, false positive and false negative cases were defined.Result There were 17 males and 6 female patients of mean age 47 (range 22-73 years). Biopsies were performed in 17 dorsal and six lumbar vertebral bodies. Adequate sample were obtained in all cases. Seventeen patients (12: tubercular pathology, 1: primary tumor, 3: metastasis, 1: osteoporotic fracture) had definitive histological/ microbiological diagnosis. Four patients had no granuloma and tumor. Two had histological features of chronic non specific inflammation. True positive cases were 17, true negative were four and false negative case were two. Overall accuracy was 92%. One patient developed small hematoma at biopsy site.Conclusion Fluoroscopy guided percutaneous transpedicular biopsy of is a safe procedure with high adequacy and accuracy and low complication rate for thoracic and lumbar vertebral body lesion.